TRANSFORMATIONAL LEADERSHIP DIMENSIONS IN DIGITAL LEARNING TRANSFORMATION FOR ISLAMIC EDUCATION QUALITY - Erma Listiyani; Muhammad Khoiruddin; Sukarman Sukarman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
Digital learning transformation has become a strategic agenda for improving the quality of Islamic education in the era of digital disruption. This study aims to formulate the contribution of transformational leadership dimensions to the implementation of digital learning for improving the quality of Islamic education. This study employed library research with a qualitative approach. Data were collected through documentation of national and international journal articles, proceedings, books, official reports, and relevant policy documents. The data were analyzed using content analysis through data reduction, concept categorization, meaning interpretation, synthesis of findings, and conceptual formulation. The findings show that the four dimensions of transformational leadership contribute to digital learning transformation. Idealized influence builds digital-ethical role modelling through integrity, data security, academic honesty, and respectful digital communication. Inspirational motivation strengthens an Islamic digital transformation vision by directing technology use toward learning quality, access, institutional service, and Islamic identity. Intellectual stimulation encourages reflective digital pedagogical innovation through creative digital content, collaborative applications, learning analytics, problem-solving, and ethical AI utilization. Individualized consideration ensures inclusive and sustainable transformation through teacher needs mapping, gradual training, coaching, professional learning communities, and personal support. This study concludes that digital learning transformation in Islamic education should not be understood merely as technology adoption, but as a value-based, competence-oriented, and system-supported process. Transformational leadership becomes a strategic framework for integrating Islamic values, teacher digital competence, institutional governance, and quality improvement.